Hands-on science and technology : an inquiry approach. - Lawson, Jennifer, 1959- (Portage & Main Press, 2018)
Hands-On Science and Technology: An Inquiry Approach is filled with a year’s worth of classroom-tested activity-based lesson plans. The grade 6 book is divided into four units based on the current Ontario curriculum for science and technology. Biodiversity Flight Electricity and Electrical Devices Space This new edition includes many familiar great features for both teachers and students: curriculum correlation charts; background information on the science and technology topics; complete, easy-to-follow lesson plans; reproducible student materials; materials lists; and hands-on, student-centred activities. Useful new features include: the components of an inquiry-based scientific and technological approach Indigenous knowledge and perspective embedded in lesson plans a four-part instructional process—activate, action, consolidate and debrief, and enhance an emphasis on technology, sustainability, and differentiated instruction a fully developed assessment plan that includes opportunities for assessment for, as, and of learning a focus on real-life technological problem solving learning centres that focus on multiple intelligences and universal design for learning (UDL) land-based learning activities a bank of science related images